Examining the Distinct Antecedents of E-Mail Habits and its Influence on the Outcomes of a Phishing Attack. Issue 5 (1st June 2015) - Vishwanath, Arun
Abstract: While research has linked social media phishing susceptibility to individual Facebook habits, the underlying process by which habits lead to victimization and the extent to which it explains e-mail-based phishing remains unclear. The study compared the antecedents and consequences of e-mail habits and cognitive processing on the outcome of a simulated phishing attack. E-mail habits were rooted in stable personality dimensions of conscientiousness and emotional stability, while cognitive processing was premised on contextual information adequacy considerations. Interestingly, habits and processing jointly influenced the outcome of the attack: Systematic processing attenuated phishing susceptibility by a small factor; the cumulative effects of heuristic processing and e-mail habits, however, caused a fourfold increase in likely victimization, overwhelming any advantage from detailed processing.